Perancangan Kompor Berbahan Bakar Oli Bekas dengan Sistem Penyalaan Pemantik Elektrik - Hisyam, Muhammad Afif; Budiono, Heru Santosa; Purnomo, Sigit Joko (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Sed oil is a hazardous waste that has the potential to pollute the environment if not managed properly. This study aims to design and analyze a used oil-fueled stove with an electric ignition system to improve efficiency and safety. The research method includes the design stage, material selection, calculation and numerical simulation using static analysis. The calculation results show a tank volume of 1.61 L, an oil flow rate of 0.63 m/s, a discharge of 0.179 L/s, and a fuel consumption of 0.0536 L/minute for 30 minutes of operation. Static simulation using von misses analysis produces a maximum stress of 3.128 x 10² kgf and a minimum of 1.341 x 10 ̄ ˡ kgf. The maximum displacement value is 7.717 x 10 ̄ ² mm and a minimum of 1.000 x 10 ̄ ³º mm. A safety factor (FOS) of 8.1 indicates that the stove structure is safe against working loads and operational temperatures. The electric ignition system is capable of producing high-voltage sparks, accelerating the oil combustion process.